Taxes, Inflation and Corporate Financial Policy - SCHALL, LAWRENCE D. (Journal of Finance, 1984)
ABSTRACT This paper examines inflation‐induced distortions in personal and corporate income taxes and discusses the implications for corporate dividend and financial structure policies and for shareholder unanimity. The tax effects relating to capital gains and debt interest cause changes in aggregate corporate borrowing and lead to equilibrium tax relationships which differ from the zero‐inflation tax relationships.